Novice Teachers’ Encounters with Fabrications - Lebedytė-Mečionienė, Indrė (Pedagogika, 2023)
The establishment of new public management in the education sector has brought productivity and efficiency to the forefront of schools. Performance must now be measurable and comparable. Educational institutions not only compete with each other for their place in comparison tables but also in the education market. The introduction of performativity, monitoring systems, and information production in education has not only changed what educators, researchers, and students do but also who they are. Novice teachers’ experience of the reality of education was investigated using the thematic analysis method and the critical theory epistemological approach. Various fabrications that exist within the educational system were revealed. For novice teachers, these fabrications are deemed unacceptable and are seen as deficiencies. Therefore, it is crucial to identify these fabrications and find solutions to eliminate these perverse practices in order to retain teachers in the profession. Fabrications related to individual activities, such as the demand for documents that no one reads, the illusion of improving teachers’ qualifications, duplicity in relationships, and falsification of grades, were identified during analysis. Fabrications at the organizational level, such as the systematic devaluation of the value of grades, prioritization of the school prestige and image, and fabrication of documents at the national level that generate other fabrications, were also identified.